2004
DOI: 10.1158/1078-0432.ccr-0436-03
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RhoA, Rac1, and Cdc42 GTPases Is Associated with Progression in Testicular Cancer

Abstract: The Rho family of GTPases are involved in actin cytoskeleton organization and associated with carcinogenesis and progression of human cancers. We investigated the roles of Rho family GTPases, prototypes RhoA, Rac1, and Cdc42, and the major downstream targets of RhoA, ROCK-I, and ROCK-II in testicular cancer. We quantified protein expression in paired tumor and nontumor samples from surgical specimens from 57 consecutive patients with testicular germ cell tumors using Western blotting. Protein expression of Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
177
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(184 citation statements)
references
References 29 publications
6
177
0
1
Order By: Relevance
“…based on a number of studies, upregulated RhoA is associated with tumor progression in different types of cancer (33)(34)(35) and RhoA activation promotes the migration of cervical, colon and hepatocellular carcinoma (36)(37)(38). However, significantly downregulated expression of RhoA was demonstrated in human conventional RCC compared to that in normal kidney tissues (17) and activated RhoA has specifically been shown to inhibit the migration of breast and prostate cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…based on a number of studies, upregulated RhoA is associated with tumor progression in different types of cancer (33)(34)(35) and RhoA activation promotes the migration of cervical, colon and hepatocellular carcinoma (36)(37)(38). However, significantly downregulated expression of RhoA was demonstrated in human conventional RCC compared to that in normal kidney tissues (17) and activated RhoA has specifically been shown to inhibit the migration of breast and prostate cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…137,138 The classical Rho GTPases, RhoA, Rac1 and Cdc42, have been shown to be important for the progression and metastasis of different human tumors including breast cancer, liver cancer, melanoma, testicular cancer and ovarian cancer. [139][140][141] RhoA appears to be involved in almost all stages of tumor progression. For example, in gastric cancer cell lines, RhoA is found to be hyperactive and its suppression leads to partial inhibition of the proliferation phenotype.…”
Section: Rho Gtpases In Cancermentioning
confidence: 99%
“…In support of this, preclinical studies have shown beneficial effects of ROCK inhibition on tumor incidence rates, volume, invasiveness and metastasis (Itoh et al, 1999;Somlyo et al, 2000;Nakajima et al, 2003;Ying et al, 2006;Ogawa et al, 2007;Xue et al, 2008). In addition, elevated ROCK1 and/or ROCK2 expression have been detected in several human cancers, which correlated with poor outcome (Kamai et al, 2002(Kamai et al, , 2003(Kamai et al, , 2004Abe et al, 2008). Although alterations in the regulation of ROCK1 signaling as an important contributory factor to human cancer may be well accepted, this is the first report of ROCK1 activation as a direct consequence of somatic mutations.…”
mentioning
confidence: 96%